Hubungan Antara Produk Domestik Regional Bruto dan Pengangguran di Provinsi Jawa Tengah Tahun 2011-2020 - Rosita Alfiansyah Zunaida; Mulyo Hendarto Robertus (Universitas Diponegoro, 2022)
Labor is one of the indicators used to see the development and economic conditions of a region. Economic growth and the growth of the Labor Force are traditionally considered as one of the positive factors that spur economic growth. Central Java Province is one of the provinces in Indonesia which in 2020 through the 2020 Population Census has a total population of 36,516,035 people, occupying the third position among the provinces in Indonesia with the highest population. With the population increasing every year, the number of unemployed also increases because the labor force cannot be absorbed into the available jobs. The value of labor absorbed in an economic sector can describe the workforce that is included in the labor force that is able to be absorbed by economic sectors. The relationship between GRDP and unemployment is explained through Okun's Law. Okun's law states that for every 2 percent decrease in GRDP related to potential GRDP, the unemployment rate increases by about 1 percent so it can be concluded that the unemployment rate has a negative relationship with GRDP growth. The method used in this study is panel data regression method using the REM model. The data used in this study is data on the GDP and unemployment of Central Java Province in 2011-2020. The result of this research is that the GRDP variable has a positive relationship to the unemployment variable. This is not in line with Okun's Law which explains that the relationship between GRDP and unemployment has a negative relationship. So it can be concluded that Okun's Law cannot be applied in cases in Central Java Province.